2000
DOI: 10.1016/s0024-3841(99)00032-7
|View full text |Cite
|
Sign up to set email alerts
|

How report verbs become quote markers and complementisers

Abstract: In many languages across the world, verbs reporting speech, thoughts and perceptions (also referred to as quotative verbs) grammaticalise into quote markers and/or complementisers. This paper analyses the change of the items kua and fen in the Austronesian languages Tukang Besi and Buru, as originally full lexical 'report' verbs that became open to reinterpretation as grammatical items after having undergone 'semantic bleaching'. It is proposed that the 'semantic bleaching', which crucially involves loss of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(31 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Coulmas 1986, Verschueren 1987, Maldonado 1991, Lucy 1993, Thompson 1996, Güldemann & von Roncador 2002, Holt & Clift 2007, Buchstaller & van Alphen 2012. The focus of the other broad line of research is on the verbs used to introduce direct speech with special attention to the syntactic behaviour of the verbs (Dirven et al 1982, Levin 1993, De Roeck 1994, Goldberg 1995, Klamer 2000, Suñer 2000 or their semantic properties (Wierzbicka 1987, Lehrer 1988, Rudzka-Ostyn 1988, Faber & Mairal Usón 1999, Kissine 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Coulmas 1986, Verschueren 1987, Maldonado 1991, Lucy 1993, Thompson 1996, Güldemann & von Roncador 2002, Holt & Clift 2007, Buchstaller & van Alphen 2012. The focus of the other broad line of research is on the verbs used to introduce direct speech with special attention to the syntactic behaviour of the verbs (Dirven et al 1982, Levin 1993, De Roeck 1994, Goldberg 1995, Klamer 2000, Suñer 2000 or their semantic properties (Wierzbicka 1987, Lehrer 1988, Rudzka-Ostyn 1988, Faber & Mairal Usón 1999, Kissine 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, verbs like 'say' very frequently grammaticalize as complementizers (Gouffé 1970, Kaisse & Shaw 1985, Ebert 1991, Botne 1998, Deutscher 2000, Klamer 2000, Güldeman 2002). The present approach is also at odds with much of the previous literature in terms of the treatment of noun augments.…”
Section: Comparison Against Previous Analysesmentioning
confidence: 99%
“…Typological research has shown that the reanalysis of a speech act verb 'say' and its grammaticalization into a complementizer have occurred more widely than previously thought, for example in Austronesian languages (Klamer 2000), Sinitic languages (Chappell 2008), and…”
Section: The Grammaticalization Of 'Say' Complementizersmentioning
confidence: 99%